Safety evaluation of the food enzyme bacillolysin from the non‐genetically modified Bacillus amyloliquefaciens strain GNP - EFSA Panel on Food Contact Materials, Enzymes and Processing Aids (CEP); Claude Lambré; José Manuel Barat Baviera; Claudia Bolognesi; Pier Sandro Cocconcelli; Riccardo Crebelli; David Michael Gott; Konrad Grob; Evgenia Lampi; Marcel Mengelers; Alicja Mortensen; Gilles Rivière; et al. (EFSA Journal, 2023)
Abstract The food enzyme bacillolysin (EC 3.4.24.28) is produced with the non‐genetically modified Bacillus amyloliquefaciens strain GNP by DSM Food Specialties B.V. The production strain qualifies for the qualified presumption of safety (QPS) approach to safety assessment. The food enzyme is intended to be used in nine food manufacturing processes: processing of cereals and other grains for the production of baked products, cereal‐based products other than baked, brewed products and distilled alcohol; processing of dairy products for the production of flavouring preparation and modified milk proteins; processing of meat and fish products for the production of protein hydrolysates; processing of plant‐ and fungal‐derived products for the production of protein hydrolysates and plant‐based analogues of milk and milk products. Since the food enzyme–total organic solids (TOS) is not carried into distilled alcohols, dietary exposure was estimated only to the remaining eight food processes. Exposure was estimated to be up to 17.934 mg TOS/kg body weight per day in European populations. As the production strain qualifies for the QPS approach to safety assessment and no issue of concern arose from the production process, no toxicological studies other than the assessment of allergenicity were required. A search for the similarity of the amino acid sequence of the food enzyme to known allergens was made and no match was found. The Panel considered that the risk of allergic reactions upon dietary exposure cannot be excluded (except for distilled alcohol production), but the likelihood is low. Based on the data provided, the Panel concluded that this food enzyme does not give rise to safety concerns, under the intended conditions of use.